《从“同性恋爱”到“走向革命”：《我的童年》与郭沫若日后的“自我改造”》= “From homosexuality to revolution : on the years of my boyhood and Kuo Mo-jo’s later-day ‘‘self-reform’‘ - 許维贤 Hee, Wai Siam (2014)
〈我的童年〉詳實記載郭在少童時期的同性戀愛經歷。本文對照不同版本的〈我的童年〉，把同性戀置於郭沫若一系列的自敘傳、詩文和私函進行追踪。本文發現走向革命後的郭，縱使在日後不斷對自己進行自我改造,也大量修改自己前期的作品。諸多刪改中，唯獨對〈我的童年〉的同性戀描寫只字未刪，這足見郭對同性戀即使從未張揚，但亦不刻意避諱。只字未刪不意味著作者對同性戀毫無愧疚。同性戀記憶對郭而言，始終是他在危難期間發憤而抒懷國家衰敗與革命挫折的徵候。晚年郭跟少年陳明遠的魚雁往返，不但可被視為〈我的童年〉返老還童的極度含蓄版，亦是他對革命挫折的自我救贖。本文也指出郭一生從「同性戀愛」到「走向革命」的徵候「自我改造」不是學者以為的「自我昇華」，而是郭的「個體神話」邁向「集體神話」的「自我形塑」過程中，同性情慾的性能量，被極端國族主義壓抑變形後，不幸轉化為法西斯衝動的精神能量，朝向極權領袖強大磁場靠攏的結果。那是一種自我理想化的人格賦予愛國主義的形式。郭的同性戀在「自我改造」多年後，並沒有從根本上被革命論述去除，反而成為他每次面對革命挫折後，從理想化人格撤退到個人化人格的自我想像和自我保護。每當革命的進程面臨險境，他會潛意識地通過書寫，重新召喚被壓抑的同性愛慾望，作為一種對當下精神環境的回應。同性戀成為郭一生吸納與排除革命幻滅的情感力量依據。Since this century, facing new development of neoliberalization in Taiwan, whether anthropology in Taiwan would utilize this chance to avoid being periherized? By the result of a study case of Taketonpu Bunun, we are not only sure that local societies and cultures in Taiwan have had fundamental changes and entered a new age, but also sure further that anthropology in Taiwan has had some major difficulties in studying the contemporary: lacking historical consciousness or the consciousness of the times makes the study de-contextualized, the traps and burdens of the concepts derived from modernity, neglected psychology’s interpretive turn, without holding the totality of the studied socio-culture, the limitation of our past thoughts, etc. These prevent us from treating validly new issues in the contemporary. The solution is to go back to our fieldwork in historical context or in the context of the times for the ethnography which is a mode of inquiry. Of course, this kind of ethnography is concerned with various aspects of the studied in necessary width and depth. On the other hand, besides reflection on the past thoughts and necessary reinvention or creation of new knowledge, we need more the capability to synthsize rather than analyze the data for finding out the studied’s major concerns by which we would contribute to the emerging world anthropologies with multiple centers.